English Language Education as a Social Divider: A Case Study - Shrestha, Parshu Ram (Journal of Janta Multiple Campus, 2024)
This study explores how English language teachers and their students in Nepal have experienced about using English as a medium of instruction in their classroom. A case study was conducted at a public school in Sunsari district in Nepal where English language has been taught to the students in English medium classes and Nepali medium classes separately for some years. Class observation and in-depth interviews with the participants were devised as tools for collecting the data. Interpretive phenomenological approach helped the researcher to conclude that EMI has created a social division between the English language teachers and their students who use it and who do not in their classroom.